Прогнозування якісних технічних показників плодів яблуні залежно від стресових абіотичних факторів - Сердюк, Марина Єгорівна; Сердюк, Марина Егоровна; Serdyuk, Maryna; Байбєрова, Світлана Сергіївна; Байберова, Светлана Сергеевна; Bayberova, Svitlana (Харк. держ. ун-т харчування та торгівлі, 2014)
UK: Розглянуто вплив стресових абіотичних факторів на формування якісних технічних показників плодів яблуні. Установлено, що основним факторним показником технічних характеристик якості яблук в умовах Південної степової підзони України слід уважати середню масу плоду. Розроблено математичну модель прогнозування даного показника залежно від стресових погодних чинників. EN: The estimation of the influence of weather factors on the apple fruits qualitytechnical indicators in the south of Ukraine steppe zone is presented. It has been found that the main factorial of an apples quality indicator should be considered an average weight of the fruit. The correlation analysis results have revealed the main stress weather factors in the region, having the greatest impact on the weight of apples. These included: the amount of active temperatures during the last month of the fruit ripening and the yearly quantity of days with precipitation greater than 1 mm. Methods of variation statistic were used for the analysis of the experimental data and the end result forecasting. The function of linear dependence: Y = a0 + a1X1 + +a2X2 +... + anXn was used for a multifactor model forming. As a result a multi-factor model that allowed forecasting the mass of apple fruit depending on the influence of abiotic stress factors has been developed.
Forecasting quality technical indicators of apple fruits depending on stress abiotic factors
Keywords: товарність; маса; яблука